2016
DOI: 10.1038/srep36456
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Non-Peptidic Agonist of the Ghrelin Receptor with Orexigenic Activity In vivo

Abstract: Loss of appetite in the medically ill and ageing populations is a major health problem and a significant symptom in cachexia syndromes, which is the loss of muscle and fat mass. Ghrelin is a gut-derived hormone which can stimulate appetite. Herein we describe a novel, simple, non-peptidic, 2-pyridone which acts as a selective agonist for the ghrelin receptor (GHS-R1a). The small 2-pyridone demonstrated clear agonistic activity in both transfected human cells and mouse hypothalamic cells with endogenous GHS-R1a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…For that reason, they display signaling pathway characteristics similar to those of the endogenous ligand, ghrelin. In addition, we showed that pyridone, a novel nonpeptide GHSR-1a agonist, recently identified in our laboratory (44), increases Ca 2+ influx (EC 50 , 3.1 mM), but is unable to regulate GHSR-1a internalization, even at 10 mM, nor does it increase b-arrestin-1 recruitment, suggesting a signaling bias and functional selectivity toward G-protein-dependent signaling.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…For that reason, they display signaling pathway characteristics similar to those of the endogenous ligand, ghrelin. In addition, we showed that pyridone, a novel nonpeptide GHSR-1a agonist, recently identified in our laboratory (44), increases Ca 2+ influx (EC 50 , 3.1 mM), but is unable to regulate GHSR-1a internalization, even at 10 mM, nor does it increase b-arrestin-1 recruitment, suggesting a signaling bias and functional selectivity toward G-protein-dependent signaling.…”
Section: Discussionmentioning
confidence: 81%
“…To investigate the roles of these GHSR-1a ligands in b-arrestin-dependent signaling, b-arrestin-1 recruitment was analyzed in a U2OS cell line. Ghrelin, MK-0677, and L692,585 (500 nM each) showed a classic agonist response increasing b-arrestin-1 recruitment; however, this effect was not observed after treatment with 500 nM pyridone, which had been identified as a novel nonpeptide GHSR-1a agonist in our laboratory (44) (Fig. 2B).…”
Section: Potency and Efficacy Profiles Of Ghsr-1a Ligandsmentioning
confidence: 80%
See 1 more Smart Citation
“…GHSR-1a mediated changes in intracellular Ca 2+ were recorded on a High-Throughput Cellular Screening System (Molecular Devices Corporation, Sunnyvale, San Jose, CA, USA). Ca 2+ mobilisation assays were performed according to a protocol modified from a previously described method [ 39 ]. Stably transfected human embryonic kidney (HEK293A) cells overexpressing GHSR-1a were seeded in sterile 96-well microtiter plates with black-walled and clear-bottomed wells (3904, Costar, Fisher Scientific, Dublin, Ireland) at a density of 2.5 × 10 4 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium imaging took place for HEK-GHSR-1a cells seeded on a 12-well plate at 2.0 × 10 5 cells/mL two days before the assay according to a previously described method [ 39 ]. The day before the assay, media was swapped to serum-free.…”
Section: Methodsmentioning
confidence: 99%